DERAJAT DEHIDRASI DAN STATUS GIZI DENGAN LAMA RAWAT INAP PADA BALITA DENGAN DIARE AKUT - A. Mudrikah H. Dirgahayu; Robby Kalew; Johan B. Bension (PAMERI, 2019)
Acute diarrhea is one of diseases commonly affecting infants and children. Several indications for hospitalization of infants with acute diarrhea include dehydration and malnutrition. This research was carried out to understand the relation of dehydration level and nutritional status to duration of hospitalization in infants with acute diarrhea. The study was conducted using comparative analytical research with cohort prospective approach in RSUD DR. M. Haulussy Ambon during March -June 2017, within the number of samples in the research of 77 infants chosen using consecutive sampling technique. Analysis of bivariate used in this study was chi-square test. According to analysis of bivariate, there is no significant relation between dehydration level and duration of hospitalization in infant patients with acute diarrhea with the value of p=0.110 and RR=3.333 (CI 95% = 0.732–15.185), similarly, there is no significant relation between nutritional status and duration of hospitalization in infant patients with acute diarrhea with the value of p=0.377 and RR=1.700 (CI 95% = 0.369–7.842).